ANALISIS MOTIVASI KERJA DALAM MENINGKATKAN KINERJA PEGAWAI PADA KANTOR KECAMATAN CITEUREUP KABUPATEN BOGOR - Sahnaz Nadia A Gazali; R. Akhmad Munjin; Ginung Pratidina (Jurnal Governansi, 2022)
The implementation of the Policy on the Arrangement and Empowerment of Street Vendors in Sukabumi City has not yet been fully realized. Some indications of this are that the goal of realizing a clean, beautiful, orderly, and safe city with adequate and environmentally sound urban facilities and infrastructure has not been achieved properly. This means that the city's chaos due to the presence of street vendors still occurs in the Sukabumi City area. Furthermore, many street vendors have felt the impact of the Covid-19 pandemic, which has resulted in a decrease in their income of street vendors. In addition, the economic environment also affects the process of implementing policies for structuring and empowering street vendors. Some of the budget for structuring and empowering street vendors has been eroded and diverted to the budget for handling the Covid-19 pandemic in the Sukabumi City area. However, from these various problems, the Regional Government of Sukabumi City continues to strive to realize the arrangement and empowerment of street vendors for the better, one of which is by building the Pelita Market which will serve as a trading centre for street vendors with an orderly and safe arrangement so as to provide comfort to the street vendors. Street vendors and the people of Sukabumi City.